Reflexões sobre diálogo sob efeito da clínica de linguagem com afásicos - Tesser, Evelin (2007)
Aphasic speech constitute a challenge for language therapy for presenting itself as hesitant, elliptical and incomplete characteristics which often produces a cohesion disarrange and, consequently, a dialogical disturbance. Aphasia can be taken as an striking example of what has been described by Lier-DeVitto (2006) as a disturbance in speech which destroys the illusion of the speaker of being in control of hers/his own speech, thus tearing apart the social tissue in which it is involved (my emphasis). Dialogue - even when ambiguous and full of misunderstandings is the privileged bonding mechanism between speakers. It constitutes, thus, the basis for clinical intervention. In fact, it is through dialogical processes that the aphasic patient changes his/her position in relation to its own speech or the speech of others. It is, therefore, of importance to reflect upon the complexity and heterogeneity of dialogues as well as on the interactional asymmetry which is alleged part of the dialogical process in clinical settings (SALAZAR-ORVIG 1998, among others) an asymmetry which does not take into account the specific theoretical/clinical features of dialogues involving normal and symptomatic speeches. This dissertation assumes dialogue as an asymmetric exchange (in the sense of a non-coincidence between speakers) and aims at discussing the nature and functions of dialogical processes in various therapeutic approaches. Such a point of view distances itself both from behavioristic and from social approaches based on the notion of shared knowledge it is, instead, directed towards the idea of dialogue as the driving force behind the changes that take place in patients speech. The discussion will be illustrated by clinical material